1993
DOI: 10.1093/oxfordjournals.annonc.a058495
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of cisplatin and 120-hour continuous infusion of 5-fluorouracil in patients with advanced pancreatic adenocarcinoma

Abstract: The combination of CDDP and 5-FU in continuous infusion seems an active and well tolerated treatment in APC and will be compared to standard therapy in a multicentric randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Cisplatin combined with 5-FU appears to be promising in metastatic pancreatic carcinoma, with a 26% response rate and a median survival rate of 7 months in a phase II trial (10). In a randomized trial comparing 5-FU with 5-FU plus cisplatin, FU-cisplatin was found to be superior to FU in terms of response and PFS, but not OS (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cisplatin combined with 5-FU appears to be promising in metastatic pancreatic carcinoma, with a 26% response rate and a median survival rate of 7 months in a phase II trial (10). In a randomized trial comparing 5-FU with 5-FU plus cisplatin, FU-cisplatin was found to be superior to FU in terms of response and PFS, but not OS (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin combined with 5-FU appears to be promising in metastatic pancreatic carcinoma, with a 26% response rate and a median survival rate of 7 months in a phase II trial (10). In a randomized trial comparing 5-FU with 5-FU plus cisplatin, FU-cisplatin was found to be superior to FU in terms of response and PFS, but not OS (9,10). The combination of S-1 and cisplatin has also been adopted in advanced gastric cancer, based on previous studies which revealed that combination therapy with S-1 and cisplatin had promising effects with tolerable toxicity (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these small trials, prolonged (at least 24 hours) infusion 5-FU was associated with better response and survival outcomes than bolus 5-FU, again suggesting that 5-FU activity in pancreatic cancer is schedule dependent. Grade 3/4 toxicities included neutropenia (12%-23%), nausea and vomiting (12%-17%), and mucositis (up to 14%) [92][93][94][95][96][97]. Combinations of platinum compounds with gemcitabine also have demonstrated encouraging outcomes with response rates ranging from 11%-31% and median survival times of 6-8.5 months (Table 2).…”
Section: Cisplatin and Oxaliplatinmentioning
confidence: 99%
“…Although the clinical investigation of several antitumour agents has been conducted with a principal focus on fluorouracil, no agent has been found to suppress tumour growth. Also, there is no obvious improvement in the results of treatment with multiple drug therapy (Kelsen et al, 1991;Topham et al, 1991;Rougier et al, 1993;Nose et al, 1999) or the biochemical modulation of fluorouracil (Pazdur et al, 1992;Louvet et al, 1993;Weinerman and MacCormick, 1994;Bernhard et al, 1995). Gemcitabine, a nucleoside analogue, is efficacious in relieving the symptoms such as algia or general state in the case of nonscaling down of tumours (Casper et al, 1994).…”
mentioning
confidence: 99%